OPTIMUM PERFORMANCE OF STABILIZED EDE LATERITE AS AN ALTERNATIVE CONSTRUCTION MATERIAL - Bukunmi O, Adegbenle (International Journal of Engineering Technologies and Management Research, 2016)
Laterite samples from Ede area with particle components of 19.7% clay, 32.8% silt and 47.5% sand was stabilized with combined cement, lime and bitumen and test for Compressive strength, Linear Shrinkage, Permeability and Water Absorption. The stabilizers were mixed with laterite soil in different ratios and percentage. The laterite carried 90% which is constant while the three stabilizers shared the remaining 10% in varying form. After 28 days of curing, laterite stabilizer with 90% of laterite, 8% of cement, 1% lime and 1% bitumen (LCLB1) possessed compressive strength of 2.01N/mm2. It Water Absorption Capacity was 3.05%. LCLB4 stabilizer (90% laterite, 6% cement, 2% lime and 2% bitumen) has the same compressive strength with LCLB1 stabilizer but with a high Water Absorption Capacity of 4.2%. The stabilizer of 90% laterite, 3.33% cement, 3.33% lime and 3.33% of bitumen (LCLB8) has the lowest compressive strength of 0.74N/mm2 and the highest Water Absorption Capacity of 5.39%. The results shows that LCLB1 stabilizer is a better stabilizer for strength and blocks made from laterite stabilized with it stand a good alternative to sand Crete blocks in building constructions. The combination of these stabilizers in order to determine a most economical volume combination for optimum performance is highly possible and economical.